Are Antipsychotics or Antidepressants Needed for Psychotic Depression? - A Systematic Review and Meta-Analysis of Trials Comparing Antidepressant or Antipsychotic Monotherapy with Combination Treatment - Farahani, Arusha (J Clin Psychiatry, 2012)
OBJECTIVE: To perform a meta-analysis of antidepressant-antipsychotic cotreatment versus antidepressant or antipsychotic monotherapy for psychotic depression. DATA SOURCES: We performed an electronic search in PubMed/Medline, Cochrane Library and PsycINFO from inception of the data bases until 02/20/2012, without language/time restrictions. Key words were: (psychosis OR psychotic OR hallucinations OR hallucinating OR delusions or delusional) AND (depression OR depressed OR major depressive disorder) AND (random OR randomized OR randomly). STUDY SELECTION: Eight randomized, placebo-controlled acute phase studies (n=762) in adults with standardized criteria-defined psychotic depression were meta-analyzed, yielding 10 comparisons. Antidepressant-antipsychotic cotreatment was compared in 5 trials with 6 treatment arms (n=337) with antidepressant monotherapy and in 4 trials and treatment arms (n=447) with antipsychotic monotherapy. DATA EXTRACTION: Primary outcome was study-defined inefficacy; secondary outcomes included all-cause discontinuation, specific psychopathology ratings and side effects. Using random effects models, we calculated risk ratios (RR) with 95% confidence intervals (CI), numbers-needed-to-treat/harm (NNT/NNH) and effect sizes (ES). RESULTS: Antipsychotic-antidepressant co-treatment outperformed antidepressant monotherapy regarding less study-defined inefficacy (N=6, n=378, RR:0.76, CI:0.60,0.96, p=0.03, I(2)=34%; NNT=7, CI:4-20, p=0.009) and Clinical Global Impressions-Severity (N=4, n=289, ES:-0.25, CI:-0.49,-0.02, p=0.03, I(2)=0%), with trend-level superiority for depression ratings (N=5, n=324, ES:-0.20, CI:-0.44,0.03, p=0.09, I(2)=10%), but not psychosis (N=3, n=161, ES:-0.24, CI:-0.85,0.38, p=0.45, I(2)=70%). Antidepressant-antipsychotic co-treatment also outperformed antipsychotic monotherapy regarding less study-defined inefficacy (N=4, n=447, RR:0.73, CI:0.63,0.84, p<0.0001, I(2)=0%; NNT=5, CI:4-8, p<.0001) and depression (N=4, n=428, ES:-0.49, CI:-0.75,-0.23, p=0.0002, I(2)=27), while anxiety (p=0.11) and psychosis ratings (p=0.06) only trended favoring co-treatment. All-cause-discontinuation and reported side effect rates were similar, except for more somnolence with antipsychotic-antidepressant co-treatment versus antidepressants (p=0.02). Only one open, 4-month extension study (n=59) assessed maintenance/relapse prevention efficacy of antidepressant-antipsychotic cotreatment versus antidepressant monotherapy, without group differences. CONCLUSIONS: Antidepressant-antipsychotic cotreatment was superior to monotherapy of either class in the acute treatment of psychotic depression. These results support recent treatment guidelines, but more studies are needed to assess specific combinations and maintenance/relapse prevention efficacy.